Agricultural reuse of the digestate from low-cost tubular digesters in rural Andean communities - Garfí, Marianna; Gelman, Pau; Comas, Jordi; Carrasco Chilón, William Leoncio; Ferrer, Ivet (El Sevier, 2021)
This research aimed at assessing the properties of guinea pig manure digestate from low-cost tubular digesters for crops fertilization in rural Andean communities. To this end, field trials were carried out to evaluate the effect of the digestate on two common Andean crops: potato (Solanum tuberosum) and forage (Lolium multiflorum and Trifolium pratense L.). The potato yield (20–25 t ha−1) increased by 27.5% with digestate, by 15.1% with pre-compost and by 10.3% with the mixture, compared to the control. The forage yield (20–21 t ha−1) increased by 1.4% with digestate – 50% dose, and by 8.8% with digestate – 100% dose and digestate – 150% dose, compared to the control. The results suggest that the digestate is an appropriate substitute of manure pre-compost for potato fertilization. The results with forage indicate that it can be applied in a range of doses, according to the amount produced by the digester. Currently, manure is either used for cooking or as fertilizer. With low-cost tubular digesters implementation, it could be used to feed the digester, using the digestate for crops fertilization and biogas for cooking; improving household living conditions and protecting the environment. Since soil properties in rural Andean communities differ from experimental layouts, the effect of fertilizers should be re-evaluated in-situ in future research studies.